Circadian Rhythm Disturbances in Mood Disorders: Insights into the Role of the Suprachiasmatic Nucleus - Chelsea A. Vadnie; Colleen A. McClung (Neural Plasticity)
Circadian rhythm disturbances are a common symptom among individuals with mood disorders. The suprachiasmatic nucleus (SCN), in the ventral part of the anterior hypothalamus, orchestrates physiological and behavioral circadian rhythms. The SCN consists of self-sustaining oscillators and receives photic and nonphotic cues, which entrain the SCN to the external environment. In turn, through synaptic and hormonal mechanisms, the SCN can drive and synchronize circadian rhythms in extra-SCN brain regions and peripheral tissues. Thus, genetic or environmental perturbations of SCN rhythms could disrupt brain regions more closely related to mood regulation and cause mood disturbances. Here, we review clinical and preclinical studies that provide evidence both for and against a causal role for the SCN in mood disorders.